2021
DOI: 10.1037/hea0001087
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation and departments of motor vehicles: Multiple messages, implementations, and replications.

Abstract: Objective: To reduce uncertainty about the effectiveness of Departments of Motor Vehicles (DMV) interventions, we assessed the influence of several DMV-based media campaigns on organ donor registration. Method: Across 4 studies, campaigns were implemented in 8 (Studies 1-3) or 9 (Study 4) New Mexico DMVs. Three theories guided message development (i.e., efficacy, altruism, vested interest). Donor registration was the outcome measure. Results: In Study 1, both the efficacy (OR = 1.14) and altruism (OR = 1.11) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Video messaging is an effective and persuasive strategy for increasing favorable attitudes toward organ donation and donor registry enrollment. 22,31-33 We extend these findings by showing that video messaging is also effective at increasing behavioral willingness to donate VCA organs. This mirrors findings by Plana et al 34 who also demonstrated that exposure to an informational video on face transplantation increased the willingness of adults to be face donors.…”
Section: Discussionsupporting
confidence: 59%
“…Video messaging is an effective and persuasive strategy for increasing favorable attitudes toward organ donation and donor registry enrollment. 22,31-33 We extend these findings by showing that video messaging is also effective at increasing behavioral willingness to donate VCA organs. This mirrors findings by Plana et al 34 who also demonstrated that exposure to an informational video on face transplantation increased the willingness of adults to be face donors.…”
Section: Discussionsupporting
confidence: 59%
“…It is also important to consider research [ 56 , 57 ] that has found self-efficacy and vested interest are important in increasing registration rates in the Department of Motor Vehicles in the US. Fostering community belonging in this context, which has been associated with negative affect [ 39 ], may further increase the number of people who register.…”
Section: Resultsmentioning
confidence: 99%
“…The current project sought to provide an interactive, engaging, and enjoyable learning module to organ donation education efforts rooted in prior successful donation campaign efforts. 9,16,44 The program was implemented across a handful of driver education programs in the Midwest-Cleveland, Ohio and Detroit, Michigan. The major findings from this study can be categorized into two main areas-between-and within-subject analyses.…”
Section: Discussionmentioning
confidence: 99%
“…LTSL was informed by organ, eye, and tissue donation intervention best practices 9,10,43,44 After completing both challenges, participants selected a real-life narrative video, from a collection of three videos, to learn about how organ donation had personally impacted an individual or family.…”
Section: License To Save Livesmentioning
confidence: 99%
See 1 more Smart Citation